Media Komunikasi dalam Hubungan LDR Pada Mahasiswa Bimbingan Konseling Universitas Islam Jember - Ramadhan, Clarisa Sandra; Bachtiar, Choirul (Program Studi Ilmu Komunikasi, 2023)
The title of this research is Whatsapp as a Media of Communication in LDR Relationships in Counseling Guidance Students at the Islamic University of Jember. This study aims to determine the intensity of communication between Long Distance Relationship partners through whatsapp media. This study used 4 informants consisting of 2 couples, who had long-distance relationships between Jember-Lampung and Jember-Yogyakarta. This research method uses descriptive qualitative research methods with data collected through observation, interviews, and documentation. The theory used in this study is the theory of relationships in the cybernetic tradition of patterns of interaction by the Palo Alto Group. The results of this study are that the intensity of communication between long-distance couples goes well, in the morning the long-distance partners always say good morning, and tell their partners that they will be carrying out activities, and at night the long-distance partners return to communicate to ask each other questions and stories the activities carried out, apart from that when there is a conflict over long distances, they also solve it by communicating via whatsapp media. The intensity of good communication can foster a partner's trust, and harmony so that they can maintain their relationship.